2019
DOI: 10.1039/c9ra04801d
|View full text |Cite
|
Sign up to set email alerts
|

Pt and RhPt dendritic nanowires and their potential application as anodic catalysts for fuel cells

Abstract: Fuel cells have a number of benefits over conventional combustion-based technologies and can be used in a range of important applications, including transportation, as well as stationary, portable and emergency backup power systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…We have also reported that a Pt 3 Ru alloy NP-loaded carbon black (Pt 3 Ru/C) catalyst has the highest activity among Pt x Ru/C ( x = 1, 3, 4) catalysts and MCH selectivity of almost 100% . Moreover, in our preliminary experiments with Pt 3 M (M = Ru, Rh, Au, Ag, Cu) alloy NP-loaded carbon black catalysts, rhodium was observed to be the best partner for Pt, although rhodium as a single catalyst showed lower activity than platinum for catalyzing electrochemical TL and benzene hydrogenation. ,, PtRh alloy and other bimetallic catalysts have been often used as catalysts for the oxidation of species including CO, formic acid, , methanol, ,,, and ethanol. ,, However, to the best of our knowledge, there have been no reports to date about their use for electrochemical TL hydrogenation. In addition, the activity of the PtRh alloy and other bimetallic catalysts has often been evaluated as mass activity, defined as the current per total mass of Pt and Rh, because of the difficulty of evaluating electrochemical surface areas (ECSAs) of Rh and Pt individually using hydrogen adsorption/desorption peaks or oxide formation/reduction peaks.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…We have also reported that a Pt 3 Ru alloy NP-loaded carbon black (Pt 3 Ru/C) catalyst has the highest activity among Pt x Ru/C ( x = 1, 3, 4) catalysts and MCH selectivity of almost 100% . Moreover, in our preliminary experiments with Pt 3 M (M = Ru, Rh, Au, Ag, Cu) alloy NP-loaded carbon black catalysts, rhodium was observed to be the best partner for Pt, although rhodium as a single catalyst showed lower activity than platinum for catalyzing electrochemical TL and benzene hydrogenation. ,, PtRh alloy and other bimetallic catalysts have been often used as catalysts for the oxidation of species including CO, formic acid, , methanol, ,,, and ethanol. ,, However, to the best of our knowledge, there have been no reports to date about their use for electrochemical TL hydrogenation. In addition, the activity of the PtRh alloy and other bimetallic catalysts has often been evaluated as mass activity, defined as the current per total mass of Pt and Rh, because of the difficulty of evaluating electrochemical surface areas (ECSAs) of Rh and Pt individually using hydrogen adsorption/desorption peaks or oxide formation/reduction peaks.…”
Section: Introductionmentioning
confidence: 76%
“…28 Moreover, in our preliminary experiments with Pt 3 M (M = Ru, Rh, Au, Ag, Cu) alloy NPloaded carbon black catalysts, rhodium was observed to be the best partner for Pt, although rhodium as a single catalyst showed lower activity than platinum for catalyzing electrochemical TL and benzene hydrogenation. 30,31,33 PtRh alloy and other bimetallic catalysts have been often used as catalysts for the oxidation of species including CO, 34−42 formic acid, 43,44 methanol, 41,42,45,46 and ethanol. [36][37][38][39][40]47,48 However, to the best of our knowledge, there have been no reports to date about their use for electrochemical TL hydrogenation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, multi-directional efforts have been devoted to improving Pt-utilization. To this end, transition metal additives in form of Pt-M alloys 10,11 (where M represents non-Pt metals), M-core@Pt-shell nanostructures 12,13 , nanowires 14,15 , nano-rods 16,17 , nano-plates 18 , nano-dendrites 19,20 , nano-frames 21,22 , nano-chains 23 , nano-cages 24 , nanocubes 25 etc. have been demonstrated to achieve desired geometry in NC design with appropriate balance between catalytic performance and noble-metal dosage.…”
mentioning
confidence: 99%